Electronic Cigarettes for Curbing the Tobacco-Induced Burden of Noncommunicable Diseases: Evidence Revisited with Emphasis on Challenges in Sub-Saharan Africa - Nansseu, Jobert Richie N.; Bigna, Jean Joel R. (Pulmonary Medicine, 2016)
Introduction. This review examines whether electronic cigarettes (e-cigs) implementation or vulgarization in sub-Saharan Africa (SSA) could be helpful in curtailing the toll of tobacco smoking in the region. Discussion. There are about 1.3 billion smokers worldwide, with nearly 80% of them living in developing countries where the burden of tobacco-related illnesses and deaths is the heaviest. Studies report that e-cigs may facilitate smoking cessation, reduction, or abstinence and may pose only a small fraction of the risks of traditional tobacco cigarettes; e-cigs may also considerably reduce second-hand smoking. Thereby, implementation of e-cig use could help to substantially reduce the burden driven by tobacco smoking in SSA, in a particular context of lack of regulations and control policies towards this threat. However, the evidence is not clear on whether e-cigs are risk-free, especially if used in the long term. Conclusions. On the whole, if e-cigs were to be introduced in SSA, they should be strictly recommended to current and/or ex-smokers as a method to quit smoking or prevent relapse and never-smokers should be strongly encouraged to avoid using these devices. Bans on sales of e-cigs to youngsters should be legislated, e-cig advertisements prohibited, and their usage continuously controlled and monitored.